Remote testing: Sensory test during Covid-19 pandemic and beyond. (March 2022) - Dinnella, Caterina; Pierguidi, Lapo; Spinelli, Sara; Borgogno, Monica; Gallina Toschi, Tullia; Predieri, Stefano; Lavezzi, Giliana; Trapani, Francesca; Tura, Matilde; Magli, Massimiliano; Bendini, Alessandra; Monteleone, Erminio
Highlights: Remote sensory tests using video calls under panel leader guidance were performed. General guidelines to set up remote sensory testing were defined. Discriminant and descriptive (including dynamic) methods were applied. Results from remote testing and from laboratory set were similar. Remote sensory tests can be used with consumers and trained panels. Abstract: Restrictions adopted by many countries in 2020 due to Covid-19 pandemic had severe consequences on the management of sensory and consumer testing that strengthened the tendency to move data collection out of the laboratory. Remote sensory testing, organized at the assessor's home or workplace and carried out under the live online supervision of the panel leader, represents a trade-off between adequate control and the convenience of conducting testing out of the lab. The Italian Sensory Science Society developed the "Remote sensory testing" research project aimed at testing the effectiveness and validity of the sensory tests conducted remotely through a comparison with evaluations in a classical laboratory setting. Guidelines were developed to assist panel leaders in setting up and controlling the evaluation sessions in remote testing conditions. Different methods were considered: triangle and tetrad tests, Descriptive Analysis and Temporal Dominance of Sensations tests, all of which involved trained panels, and Check-All-That-Apply and hedonic tests with consumers. Remote sensory testing provided similar results to the lab testing in all the cases, with the exception of the tetrad test run at work. Findings suggest that remote sensory testing, if conducted in strict compliance with specifically developed sensory protocols, is a promising alternative to laboratory tests that can be applied with both trained assessors and consumers even beyond the global pandemic.